2023
DOI: 10.1177/13621688221144832
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Chinese university EFL learners’ academic emotions and self-regulated learning strategies: A structural equation model

Abstract: Emotional research in foreign language learning has bloomed recently, and yet there has been a call for attention to a broader spectrum of emotions experienced by learners of English as a foreign language (EFL). Whilst emotions and self-regulated learning (SRL) are both believed to play important roles in EFL learning, little is known about their interplay. To fill the void, the study intends to map out an overall status quo of Chinese university EFL students’ academic emotions and SRL strategy use and sophist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 83 publications
2
15
0
Order By: Relevance
“…Notably, higher levels of pride, joy, and hope were associated with better academic outcomes. This result is consistent with previous research efforts [ 1 , 3 , 4 , 7 , 17 , [29] , [30] , [31] ]. For instance, a longitudinal study carried out in Germany revealed a similar trajectory and indicated that positive emotions had a predictive function in the “learning performance” of German students [ 30 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Notably, higher levels of pride, joy, and hope were associated with better academic outcomes. This result is consistent with previous research efforts [ 1 , 3 , 4 , 7 , 17 , [29] , [30] , [31] ]. For instance, a longitudinal study carried out in Germany revealed a similar trajectory and indicated that positive emotions had a predictive function in the “learning performance” of German students [ 30 ].…”
Section: Discussionsupporting
confidence: 94%
“…Previous research has demonstrated a noteworthy negative relationship between various negative emotions (e.g., hopelessness, fear, shame, anger, boredom) and students' academic accomplishments. This discovery aligns with the findings of several earlier studies [ 1 , 3 , 29 ]. Negative emotions, such as hopelessness and boredom, have adverse effects on learning and academic success as they can impede information processing, diminish motivation, and divert students' attention from learning tasks.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies have extensively investigated the effectiveness of SRLL among Chinese college learners (e.g., Shen et al, 2023; Y. Zhang et al, 2016, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Self-Regulated Language Learning Among Chinese College EFL Learners Previous studies have extensively investigated the effectiveness of SRLL among Chinese college learners (e.g., Shen et al, 2023;Y. Zhang et al, 2016Y.…”
Section: Literature Reviewmentioning
confidence: 99%